Reações hansênicas : perfil clínico e resposta imunológica a antígenos recombinantes de Mycobacterium leprae - Araújo, Jonnia Maria Sherlock (2013)
Leprosy is an infectious disease of great global impact. It is associated with significant morbidity, related to both the occurrence of leprosy reactions and the development of peripheral neurological disabling injuries. Leprosy reactions are immunologically mediated complications, which presents inflammatory and potentially serious clinical forms and may also be associated with the onset of physical disabilities. There are still many gaps regarding their clinical and immunological determinants, which hinders its control. The use of recombinant antigens has been shown as an important tool for the elucidation of various immunological aspects of leprosy. This study aimed to evaluate the clinical profile associated with leprosy reactions and the immune response to recombinant antigens from Mycobacterium leprae associated with reactions. Specific objectives were: 1) to evaluate the clinical characteristics that are associated with leprosy reactions, 2) to evaluate the clinical characteristics that correlate with physical disabilities at the end of treatment, 3) to compare the immune response to recombinant antigens of M. leprae between patients with and without reactions. For evaluation of objectives 1 and 2 was developed a retrospective study based on chart analysis of leprosy patients treated at two centers of medical specialties in Sergipe. For the third objective, we developed a cross sectional study that compared the immune response (IL-2, IL-4, IL-5, IL-6, IL-10, IL-12p70, IL-13, IL-15 , IL-17a, IL-23, IL-27, INF-γ, TNF-α,TGF-β, MCP-1 and MIP-1α) after stimulation with recombinant antigens of M. leprae (MLCS, ML0276, ML2028, ML2055, ML2258, ML2531, ML2629, ML82F, ML2044, ML2380, ML2331, and LID1 PADL) and M. tuberculosis (ID93, ID83, PPD) among patients who developed or not reactions. The results of objective 1 and 2 revealed the occurrence of leprosy reactions in 40% of patients and physical disabilities in 30% of patients. It was observed that the male sex was associated with multibacillary forms and reactions. The use of low doses of corticosteroid for the treatment of reactions was independently associated with the presence of physical disability at the end of treatment for leprosy. The results of objective 3 showed that inflammatory chemokines such as MCP-1, after stimulation of recombinant antigens like ML2531 and ID93, were higher in patients who developed reactions. Thus, we emphasize the need for greater vigilance of males, as well as most appropriate treatment for patients who develop reactive episodes in order to prevent physical disabilities. The production of MCP-1 in response to antigens ML2531 and ID93 can be assayed as a marker of reactions.